2018
DOI: 10.1016/j.bbmt.2018.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Lymphoma Patients Experiencing Relapse or Progression after an Allogeneic Hematopoietic Cell Transplantation

Abstract: Outcome and management of patients who relapse after allogeneic hematopoietic cell transplantation (allo-HCT) has evolved in the recent decade. Using a multi-institutional retrospective database we report the predictive factors and survival of lymphoma patients who relapse after allo-HCT. We evaluated 495 allo-HCT recipients transplanted between 2000 and 2015 at 3 academic US medical centers. Landmark analysis evaluating predictive factors was performed at 1 month after allo-HCT relapse with a primary endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(39 reference statements)
1
1
0
Order By: Relevance
“…Our findings are partially explained by the improvement in post-relapse survival that also occurred between cohorts reflecting the improvements in disease management that have developed over this time span. Similar findings were reported in a recent retrospective review of 175 relapsed lymphoma cases post allo-HCT who were found to have an encouraging median survival post relapse of 31.7 months 20 . In contrast to survival, there was no difference in the incidence of acute GVHD over the duration of this study, which demonstrates the limited progress made in prevention of this transplant- specific complication.…”
Section: Discussionsupporting
confidence: 88%
“…Our findings are partially explained by the improvement in post-relapse survival that also occurred between cohorts reflecting the improvements in disease management that have developed over this time span. Similar findings were reported in a recent retrospective review of 175 relapsed lymphoma cases post allo-HCT who were found to have an encouraging median survival post relapse of 31.7 months 20 . In contrast to survival, there was no difference in the incidence of acute GVHD over the duration of this study, which demonstrates the limited progress made in prevention of this transplant- specific complication.…”
Section: Discussionsupporting
confidence: 88%
“…Patients who relapse after alloHCT have limited treatment options, and disease progression remains a major cause of death [42,43]. The use of CAR-T therapy after alloHCT has a theoretical concern for new-onset graft-versus-host disease (GVHD) or worsening of pre-existing GVHD.…”
Section: What Are the Critical Considerations For Using Car-t After Amentioning
confidence: 99%